2022
DOI: 10.3390/ijerph19095689
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Core-Stability Exercises Guided by a Telerehabilitation App on Trunk Performance, Balance and Gait Performance in Chronic Stroke Survivors: A Preliminary Randomized Controlled Trial

Abstract: Stroke is one of the main causes of disability. Telerehabilitation could face the growing demand and a good strategy for post-stroke rehabilitation. The aim of this study is to examine the possible effects of therapeutic exercises performed by an App on trunk control, balance, and gait in stroke survivors. A preliminary 12-week randomized controlled trial was developed. Thirty chronic stroke survivors were randomly allocated into two groups. Both groups performed conventional physiotherapy, in addition to, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 51 publications
0
52
0
Order By: Relevance
“…The literature search identified 975 studies after the duplicate articles were manually removed. Screening of 53 full-text studies revealed 11 studies that fulfilled the inclusion criteria [34][35][36][37][38][39][40][41][42][43][44]. No relevant articles were identified in the additional manual search.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature search identified 975 studies after the duplicate articles were manually removed. Screening of 53 full-text studies revealed 11 studies that fulfilled the inclusion criteria [34][35][36][37][38][39][40][41][42][43][44]. No relevant articles were identified in the additional manual search.…”
Section: Resultsmentioning
confidence: 99%
“…Extracted data are presented in Tables 1 and 2. Five studies were conducted in Europe (United Kingdom, Spain, the Netherlands, and Israel) [34,38,40,42,44] and three in Asia (South Korea and the Philippines) [36,37,39]. Other studies were conducted in North America (the United States) [41], South America (Chile) [35], and Africa (Ghana) [43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations